But Dmitry did no wrong. (Economist, 2001)
The arrest of Russian computer programmer Dmitry Sklyarov under the Digital Millennium Copyright Act (DMCA) has made evident a wave of anger from programmers who are dissatisfied with the statute. The law bans technology designed to defeat software that protects copyrighted material, but programmers are upset at the deadening effect of the DMCA on academic discussion regarding encryption and security. The federal government intends to pursue the prosecution despite the fact that neither Sklyarov nor his company made or distributed illegal merchandise.